Burns Impair Blood-Brain Barrier and Mesenchymal Stem Cells Can Reverse the Process in Mice - Yang, Jie; Ma, Kui; Zhang, Cuiping; Liu, Yufan; Liang, Feng; Hu, Wenzhi; Bian, Xiaowei; Yang, Siming; Fu, Xiaobing (Frontiers in Immunology, 2020)
Neurological syndromes are observed in numerous patients who suffer burns, which adds to the economic burden of societies and families. Recent studies have implied that blood–brain barrier (BBB) dysfunction is the key factor that induces these central nervous system (CNS) syndromes in peripheral traumatic disease, e.g., surgery and burns. However, the effect of burns on BBB and the underlying mechanism remains, largely, to be determined. The present study aimed to investigate the effect of burns on BBB and the potential of umbilical cord-derived mesenchymal stem cells (UC-MSCs), which have strong anti-inflammatory and repairing ability, to protect the integrity of BBB. BBB permeability was evaluated using dextran tracer (immunohistochemistry imaging and spectrophotometric quantification) and western blot, interleukin (IL)-6 and IL-1β levels in blood and brain were measured by Enzyme-linked immunosorbent assay. Furthermore, transmission electron microscopy (TEM) was used to detect transcellular vesicular transport (transcytosis) in BBB, and mRNA sequencing was used to measure whole transcriptome in BBB to identify the potential mechanism of transcytosis. We found that burns increased mouse BBB permeability to both 10-kDa and 70-kDa dextran. IL-6 and IL-1β levels increased in peripheral blood and CNS after burns. In addition, burns decreased the level of tight junction proteins, including Claudin-1, Claudin-5, Occludin, and ZO-1, which indicated increased BBB permeability due to paracellular pathway. Moreover, increased vesicular density after burns suggested increased transcytosis in brain microvascular endothelial cells. While mRNA sequencing revealed increased Mfsd2a level, the protein level of Mfsd2a decreased after burns. Finally, administering UC-MSCs at 1 hour after burns effectively reversed these adverse effects and protected the integrity of BBB. These results suggest that burns increase BBB permeability through both paracellular pathway and transcytosis by increasing IL-6 and IL-1β levels and decreasing Mfsd2a level, and appropriate treatment with UC-MSCs can reverse these effects and protect the integrity of BBB after burn trauma.